Experimental study of a thin water-film evaporative cooling system to enhance the energy conversion efficiency of a thermoelectric device. (15th November 2020) - Zheng, Liang Jun; Lim, Sungmook; Kim, Na Kyong; Kang, Dong Hee; Youn, Young Jik; Lee, Wonoh; Kang, Hyun Wook
Abstract: In the study, a new method to enhance the performance of a thermoelectric generator (TEG) device by utilizing the water-film evaporative cooling is proposed. An experimental device was constructed by incorporating a water-film cooling pond with a commercially available TEG. Experiments were performed to investigate the effects of the main operating conditions (ambient temperature T amb was 25 °C), TEG hot-side temperature ( T H = 50–100 °C), ambient relative humidity ( RH = 15–90%), and water-film thickness ( t water = 1–9 mm) on the TEG output performance. Additionally, the output performance of TEG under different cooling methods was compared. A TEG prototype device was constructed to generate electricity/steam using seawater evaporation cooling without external electrical energy. The results indicated that TEG hot-side temperature and water-film thickness significantly affected output performance. However, the ambient relative humidity did not considerably affect TEG output performance. Given TEG hot-side temperature T H = 100 °C, ambient relative humidity RH = 15%, the TEG prototype device-generated open-circuit voltage of U open = 1.55 V, maximum output power of P max = 290.32 mW, and a steam generation rate of 9.82 mg/s. The results showed that evaporative cooling is an innovative method to improve the performance of TEG. Graphical abstract: Image 1 Highlights: Eco-friendly evaporative cooling method to improve the thermoelectric performance. Thin water evaporation has a higher cooling capacity than traditional heat sink. Ambient relative humidity is independent factor to the thermoelectric performance. Thin film evaporator applied to freshwater production and waste heat recovery.